Coulson and Richardson's chemical engineering. Volume 3B, - Rohani, Sohrab (Butterworth-Heinemann, 2017)
Coulson and Richardson's Chemical Engineering: Volume 3B: Process Control, Fourth Edition, covers reactor design, flow modeling, and gas-liquid and gas-solid reactions and reactors. Converted from textbooks into fully revised reference materialContent ranges from foundational through to technical Added emerging applications, numerical methods and computational tools.